Transformasi Kearifan Lokal Desa Adat Tenganan Pagringsingan dalam Era Globalisasi: Interaksi Budaya Lokal dan Kapitalisme Pariwisata Global - I Dewa Gede Oka Satwika; I Made Pageh; Luh Indrayani (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Globalization has drastically changed the social structure of society, particularly in the economic and cultural sectors. This phenomenon is marked by the expansion of global capitalism through the tourism industry, targeting regions rich in tradition. In Bali, tourism plays a dual role: as an economic engine and a meeting point between local values ​​and international market demands. Consequently, challenges arise for indigenous communities to maintain the authenticity of traditions amidst the pressures of a competitive economy. As part of the Bali Aga community, the Tenganan Pagringsingan Traditional Village maintains a structured system of local wisdom passed down through generations. Its unique cultural identity is reflected in spatial planning, customary law (awig-awig), and even its heritage of gringsing textiles, which tend to be protected from outside intervention. Nevertheless, the pressures of globalization through the tourism sector force the community to adapt its culture. This process creates a dynamic between exploiting economic opportunities and efforts to maintain the authenticity of traditions to prevent them from being eroded by time. This research is to examine how the community of the Tenganan Pagringsingan Traditional Village adapts its local wisdom amidst the flow of global tourism capitalism. Furthermore, this study explores the significance of this adaptation for the preservation of local culture. Using a qualitative approach and desk study methods, the data were analyzed descriptively, referring to literature on globalization and the sociocultural dynamics of indigenous communities. This study reveals that the cultural adaptation process took place in a measured and selective manner. The community succeeded in maintaining the integrity of traditional values, social structures, and sacred rituals from the influence of commercialization, while integrating the economic aspects of tourism through the crafts and services sectors. This dynamic and compromising strategy demonstrates that globalization can be managed as an opportunity to strengthen the sustainability of local identity, rather than simply being viewed as a challenge.